Peningkatan Keberlanjutan Produksi Turus Melalui Metode Reorder Point Pada UKM Sergei Connection - Sylvia Vianty Ranita; Zubaidah Hanum; Andri Herlambang; Ruri Aditya Sari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
UKM Sergai Connection as a producer of turus is very dependent on the raw material for twine rope. This raw material is obtained from other craftsmen who also depend on the availability of coconut fiber and the weather. Calculation. Calculation of the availability of appropriate and optimal raw materials is needed so that UKM Sergai Connection does not face the problem of excess or shortage of raw material stock. This community service activity aims to help UKM Sergai Connection to find out the amount of supplies of the main raw materials for turus production. The amount of production inventory is carried out through a quantitative descriptive approach. The data obtained comes from UKM Sergai Connection. Furthermore, the data were analyzed using the reorder point method. The results of the calculations showed that UKM Sergai Connection had to reorder 12 rolls of rope per day